Legal Protection in Short Selling Transactions in The Capital Market - Putri, Erika Liza; Rahmi, Yuni; Azmi, Zul (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This study aims to: (1) examine and analyze the implementation of short selling transactions, and (2) explore and analyze the legal protection available to customers/investors involved in short selling within the Indonesian capital market. The data used in this research is obtained from library research or secondary sources, including articles, books, legal norms contained in laws and regulations, and other legal materials. The analysis is conducted using a descriptive research method, employing normative juridical approaches and comparative document analysis. The results of this study indicate that short selling is a high-risk transaction, necessitating adequate protection for investors and securities to foster a sense of security and confidence when transacting in the capital market. This protection can be provided by authoritative bodies in the capital market such as the Financial Services Authority (OJK), the Stock Exchange, KSEI/KPEI, as well as through agreements between the involved parties.